2015
DOI: 10.1007/s11707-015-0542-3
|View full text |Cite
|
Sign up to set email alerts
|

Eddy analysis in the Eastern China Sea using altimetry data

Abstract: Statistical characteristics of mesoscale eddies in the Eastern China Sea (ECS) are analyzed using altimetry sea surface height anomaly (SSHA) data from 1993 to 2010. A velocity geometry-based automated eddy detection scheme is employed to detect eddies from the SSHA data to generate an eddy data set. About 1,096 eddies (one lifetime of eddies is counted as one eddy) with a lifetime longer than or equal to 4 weeks are identified in this region. The average lifetime and radius of eddies are 7 weeks and 55 km, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…For example, smaller variances are observed on the persistent Kuroshio path on the western side of the archipelago in the ECS as compared with those on the eastern side. More intensive eddy activity in the east of the archipelago is apparently caused by influences of westward propagating mesoscale eddies as Rossby waves headed toward the eastern side of the chain of the islands (e.g., Liu et al, ; Qin et al, ). In contrast, the other high SSH variances south of Kyushu and in the Kuroshio Extension Region (cf., Kamidaira et al, ; Uchiyama, Suzue, et al, ) correspond to the areas where the Kuroshio path largely meanders, reflecting intrinsic synoptic variability of the Kuroshio.…”
Section: Model Validationsmentioning
confidence: 99%
“…For example, smaller variances are observed on the persistent Kuroshio path on the western side of the archipelago in the ECS as compared with those on the eastern side. More intensive eddy activity in the east of the archipelago is apparently caused by influences of westward propagating mesoscale eddies as Rossby waves headed toward the eastern side of the chain of the islands (e.g., Liu et al, ; Qin et al, ). In contrast, the other high SSH variances south of Kyushu and in the Kuroshio Extension Region (cf., Kamidaira et al, ; Uchiyama, Suzue, et al, ) correspond to the areas where the Kuroshio path largely meanders, reflecting intrinsic synoptic variability of the Kuroshio.…”
Section: Model Validationsmentioning
confidence: 99%
“…1). From both observational analysis 1 and statistical detection results from various satellite data sets 2, 3 , abundant eddies occur along the Kuroshio path. Most studies of such eddies (in terms of generation or interaction) are related to the Kuroshio meandering path in some specific regions, e.g., in the northern Okinawa Trough 4, 5 , between the Tokara Strait and south of Kyushu 6 , in the northeast of Taiwan Island 7 , and in the Luzon Strait 8 .
Figure 1The study area: East China Sea area with boundaries marked out by the dashed line.
…”
Section: Introductionmentioning
confidence: 99%
“…Because the mean horizontal shear (a source for barotropic instability) is an important dynamic mechanism of eddy generation, we speculate that the MPK should produce mesoscale or sub-mesoscale eddies along its two sides and with eddy size constrained by the width of MPK. These eddies are not easily visualized in the low-resolution satellite images 2 , 3 , so the drifter data and high-resolution model output are employed to detect these eddies.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of eddy generation and dissipation is diverse in different sea areas. Based on previous studies such as those conducted by Liu et al [58] that found eddies in the north Pacific subtropical band are generated through baroclinic instability and wind stress, the Qin et al [60] analysis which shows that CEs in the East China Sea are mainly affected by Kuroshio transport in addition to interference from the surrounding ocean and orographic wind blockage, and the discovery of Ji et al [59] that eddies are generated near the Kuroshio Extension Region due to horizontal shear instability, it is apparent that for different regions, eddies are generated through a wide variety of mechanisms. For example, and relevant to the current subject, Chen et al [21] suggest that for BOB eddies, baroclinic instability and the influence of wind stress are the principal mechanisms for eddy interannual variability.…”
Section: The Mechanisms For Eddy Generation and Dissipationmentioning
confidence: 99%